PENEGAKAN HUKUM DAN PERLINDUNGAN HAK-HAK TAHANAN - Chairul Idrah (Jurnal LEX SPECIALIS, 2012)
Abstract In the perspective of law, violations committed by someone the rights of others, can cause offense. In the case of an alleged violation of law has occurred, it is consistent with the mandate of Pancasila as the state that is the source of all sources of law, the right of a person suspected of committing an offense or the suspect must be protected, respected and fulfilled. Associated with respect for the rights of suspects or prisoners, it is necessary to put forward opinions expressed by Mardjono Reksodiputro that the primary purpose of law enforcement is the due process of law (due process of law), which includes the rights of suspects, defendants and prisoners protected and considered as part of the rights of citizens (civil rights), and because it's part of human rights. relating to arrest and detention, the Book of the Law of Criminal Procedure (Criminal Code) has set regulations on the arrest and detention, regulated in Article 16 and Article 31 of the Book of the Law of Criminal Procedure (Criminal Code). Today the fair and humane treatment in various fields of life especially in the criminal justice process is a concern as well as a demand and desire of the people, then all the resources and efforts will be made to get justice is very essential. Key Note : Law Enforcement, Protection of Rights